Evaluasi Kebijakan Perda Kota Medan No. 6 Tahun 2003 tentang Larangan Gelandangan dan Pengemis dan Urgensi Pembentukan Rumah Perlindungan Sosial (RPS) Kota Medan - Ritonga, Fajar; Thamrin, Husni; Ridho, Hatta (SAJJANA: Public Administration Review, 2026)
This study evaluates the effectiveness of Medan City Regional Regulation (Perda) No. 6 of 2003 on the Prohibition of Homeless, Beggars, and Immoral Practices in Medan City. Using a qualitative descriptive approach, data were collected through in-depth interviews, focus group discussions (FGD), and field observations involving key stakeholders from the Medan City Social Service, Civil Service Police Unit (Satpol PP), the North Sumatra Provincial Social Welfare Technical Implementation Unit (UPTD Pungai Sejahtera Binjai), non-governmental organizations, and academic practitioners. The findings reveal that the regulation has not produced significant outcomes in reducing the homeless and beggar population in Medan. Key weaknesses include the absence of inter-agency coordination mechanisms, inadequate rehabilitation infrastructure, outdated vocational training programs, and a legal framework that criminalizes poverty rather than addressing its root causes. The study concludes that Perda No. 6 of 2003 requires comprehensive revision grounded in the principles of human dignity, empowerment, and social justice, and proposes a multi-stakeholder governance model incorporating preventive, coercive, rehabilitative, and social reintegration components.